“THE MIGHT-HAVE-BEENS” AS METAPLOT IN JULIAN BARNES’ STORYBOOK “THE LEMON TABLE” - Elena S. Annenkova (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2021)
In the article “The Lemon Table” by Julian Barnes is analyzed from the point of view of “the mighthave-beens” plot functioning in this storybook. This plot is an essential part of the fundamental for this book plot of aging and associated with its physical and mental processes that heroes of these short stories are experienced. The analysis of the majority of the short stories makes it possible to talk about “the might-have-beens” as metaplot that ties separate short stories of this storybook with each other and forms the unity of the storybook as an artistic whole. A metaplot in prosaic text is understood as that invariant plot that permeates the texts of one or another writer, which is realized in these texts in various versions of event scenarios and expressed in a figurative-motive complex, at the ideological-thematic and narrative levels, at the level of stylistics and artistic tropes of writer’s works. “The might-have-beens” metaplot repeats and manifests itself in the short stories in its different event variations and with especial completeness and emphasis in such short stories as “Story of Mats Israelson”, “Hygiene”, “The Revival”, “Bark”, “The Fruit Cage”, “The Silence”. Thus each short story enters into dialogical relationships with other stories, due to the formed internal intertextuality of this storybook and made metatext of J. Barnes’ fictional prose, as a consequence of the invariant plot of “the might-havebeens” as the source code of the generation of meaning in the artistic consciousness of the English writer evinced in many of his other works. So the main aim of this article is to discover and analyse the plot of “the might-have-beens” that becomes metaplot and metamotif of “The Lemon Table” by J. Barnes. The elements of motif, comparativetypological, receptive-interpretive, and intertextual methods of analysis have been used in this work, which helped to achieve our aim. In “Story of Mats Israelson” the invariant of “the might-have-beens” plot is presented in its fullest expression, and this plot in different variations will be repeated in other stories of the storybook. It will become its key motif, which will be related with other central motifs of other short stories of this storybook (the motif of loneliness, love, vanity of life, old age, death and immortality). “The might-have-beens” metaplot will determine the development of event situations of the short stories with a predictable culmination of misunderstanding and dissatisfaction and with the denouement of feelings or actions that have not found their embodiment, which reveals itself in a separation, alienation or death of the heroes. “The might-have-beens” metaplot will show the peculiarities of the heroes’ characters and their reactions to life situations, which will be the result of their individual life fears and complexes, aggravated by the limit situation of imminent death. “The might-have-beens” metaplot is supported by specific chronotope, which becomes space and time of the unrealized and non-embodied. This plot and motif are evinced in the short stories of “The Lemon Book” with the help of artistic metonymy and a discourse of silence, that fully expresses the impossibility of embodying the heroes’ feelings and their deepest desires. But in any event variations, “the might-have-beens” metaplot keeps structural and semantic core that is the life path of the short stories’ heroes determined by non- embodiment of their innermost desires, intentions and expectations. However, the precise impracticability of dreams, the unfulfillment of aspirations cause the piercingly sad and universal meaning of life of the heroes of “The Lemon Table” by J. Barnes